Numerical simulations of hydraulic fracture intersecting an interbed of sandstone - Sarmadivaleh, Mohammad; Rasouli, V.; Ramses, W. (2012)
Hydraulic fracturing is a common technique used in the oil and gas industry for stimulation of tight formations in order to increase productivity. Production from unconventional reservoirs including tight gas sandstones is growing rapidly. When a hydraulic fracture approaches an interface, which could be a second formation or a small pocket of shale accumulation or sand lens, it may get arrested or cross the interface. This depends on the state of in-situ stresses, rock mass properties and the interface characteristics. This paper presents the results of numerical simulations using PFC2D corresponding to two lab experiments. The modeling carried out to investigate the effect of different parameters on the interaction mechanism. Sample I includes a sandstone block in the middle of a 15 cm mortar cube. In sample II sandstone block is located in the two sides of the mortar block. The macro properties of the samples (UCS, friction coefficient etc) used for this study were estimated from the model micro properties (bond strength, friction) which are the input to PFC models. This was done by performing several simulations including bi-axial, direct and Brazilian tensile tests from which the rock properties were determined through the plot of Mohr Circles corresponding to different stress levels. Similarly, micro and macro hydraulical properties were estimated using permeability simulation tests. A hydraulic fracture was initiated in the centre of the sample and model response was monitored. The results are presented here and conclusions are made. © 2012 Taylor & Francis Group, London.